Herbicide Resistance Management and Sustainable AG: An Industry Perspective. (1st October 2013) - Soteres, John; Glasgow, Les; Peterson, Mark; Obrigawitch, Tim; Evans, Richard; Strek, Harry; Pawlak, John; Wilson, Sam
Among the pests that challenge crop production, weeds are the most constant threat and the most costly in terms of yield losses. Historically, weed control progressed from the days when cultural practices such as mechanical tillage and hand hoeing were the main methods to manage weeds to the use of herbicides, which are the primary tool used in advanced agricultural production systems today. The effectiveness of existing herbicide assets is directly related to achieving the major goals of Sustainable Agriculture (www.sare.com). Herbicides improve crop productivity, which reduces land needed to feed a growing population and is the key technology facilitating use of conservation tillage practices with their associated environmental benefits. However, the benefits of herbicides are being threatened by the evolution of weed populations that exhibit resistance to individual herbicides or herbicide groups and, in some cases, by the evolution of weed populations with resistance to more than one herbicide or herbicide group. An example of the impact of resistance on farming systems includes that of Lolium rigidum, a major weed in Australian small grains production, which has evolved resistance to most of the major cereal-selective herbicides. Australian farmers have resorted to draconian measures, such as burning and crushing weed seed at harvest, to help manage these weed populations. Similarly a lack of new herbicide modes of action to control resistant Alopecurus myosuroides (blackgrass) in cereals in Europe has in some situations resulted in a return to deep plowing practices in the fall to bury weed seed and thus reduce their germination. The control of Amaranthus spp. (pigweeds) in some cropping systems in certain areas of the US has become a problem because populations have evolved resistance to many different herbicides. Strengthening stewardship programs around existing herbicides and developing new herbicide options are both critical to the long term sustainability of crop production systems and to achieving the goals of Sustainable Agricultural systems. In response to the threat of resistance, the major herbicide manufacturers formed a committee, the Herbicide Resistance Action Committee or HRAC to promote industry stewardship programs and fund research activities of common interest. Global HRAC was founded in 1989 and is composed of technical representatives from member companies. Global HRAC works in alignment with Crop-Life International. Information about HRAC can be found at www.hracglobal.com. To fulfil its mission, HRAC has formed chemistry and topic focused working groups as well as area specific groups to identify and fund basic and applied research, support resistance focused workshops and symposia, and produce educational materials in cooperation with weed science societies around the world. These represent a few of its activities. HRAC also helped establish and continues to support an online global weed resistance database (www.weedscience.org), The International Survey of Resistant Weeds, developed and independently managed by Dr. Ian Heap to record and track spread of herbicide resistant weeds.